2002
DOI: 10.1097/00043764-200210000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index and Health Status in Firefighters

Abstract: This study evaluates the usefulness of body mass index (BMI) as a preventive screening tool for general health and duty fitness status among firefighters. Two major BMI categorization methods were used: (1) "standard" [low (< 27), medium (> or = 27 < 30), high (> 30)]; and (2) WHO [(normal (< 25), overweight (> or = 25 < 30), obese (> or = 30 < 39), morbidly obese (> or = 39)]. Using the "standard" categorization, nearly 60% of individuals had medium or high BMI's; using the World Health Organization categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 14 publications
8
68
2
Order By: Relevance
“…Clark, Rene, Theurer, et al found that 80.7% of the firefighters from their study were obese or morbidly obese; this caused a negative relationship between their weight and V O2 max [21]. BMI could be a useful variable when identifying health levels of candidates for rescue groups and deciding on measures improving their performance.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Clark, Rene, Theurer, et al found that 80.7% of the firefighters from their study were obese or morbidly obese; this caused a negative relationship between their weight and V O2 max [21]. BMI could be a useful variable when identifying health levels of candidates for rescue groups and deciding on measures improving their performance.…”
Section: Discussionmentioning
confidence: 87%
“…BMI measures an individual's weight and height and is useful to identify firefighters' health levels [21]. Body fat percentage was measured with Faulkner's equation [24]: body fat percentage = (triceps + subscapular + suprailiac + abdominal skin × 0.153) + 5.783.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although body mass index (BMI) has been the most widely used adiposity measure at wellness and fitness (WEFIT) programs for firefighters across the nation (Clark et al 2002;Donovan et al 2009;Soteriades et al 2005;Tsismenakis et al 2009) as for other occupational groups (Alasagheirin et al 2011;Caban et al 2005;Escoto et al 2010;Sieber et al 2014), there has been a strong skepticism as to whether BMI is a valid measure for adiposity among firefighters (Choi et al 2011;Haddock et al 2011;Jitnarin et al 2013;Poston et al 2011) because of selfselection into the occupation and the possibility of building musculature through on-the-job physical training. Two assumptions underlying firefighter skepticism are: (1) BMI may overestimate the prevalence of overweight and obesity among firefighters because of its intrinsic inability to differentiate fat body mass and lean body mass and (2) other anthropometric adiposity measures such as waist circumference and skinfold-based percent body fat may be more strongly associated with biological CVD risk factors among firefighters than BMI (Choi et al 2011).…”
mentioning
confidence: 99%